The Obstacles in Using Distance Education in Private and International Schools in Riyadh During the Corona Pandemic Period from the Viewpoint of School leaders - Al Amer, Hanan Salem Abdullah (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to identify the obstacles in using distance education in private and international schools in Riyadh during the Corona pandemic period from the viewpoint of school leaders, and identifying the statistically significant differences in the responses of the study sample according to the following variables (gender, number of years of experience, number of training courses related to information technology). The study used the descriptive approach, in which the study population consisted of leaders from private and international schools in Riyadh during the Corona pandemic, a simple random sample was taken from the study population in the size of (687) leaders, the study relied on the questionnaire as a tool to obtain the sample responses. The study came out with the following results: The estimate of the sample members (school leaders) regarding the obstacles in using distance education in private and international schools in Riyadh during the Corona pandemic period was 65.3%, indicating an average score. The absence of statistically significant differences in the responses of the study sample individuals about the obstacles in using distance education in private and international schools in Riyadh during the Corona pandemic period from the viewpoint of school leaders according to the variable (gender). The absence of statistically significant differences in the responses of the study sample individuals about the obstacles in using distance education in private and international schools in Riyadh during the Corona pandemic period from the viewpoint of school leaders depending on the variable (number of years of experience). The absence of statistically significant differences in the responses of the study sample individuals about the obstacles in using distance education in private and international schools in Riyadh during the Corona pandemic period from the viewpoint of school leaders according to the variable (number of training courses related to information technology). The study recommended the necessity of intensify efforts to provide Internet access to remote areas that are not included in the Internet distribution services to ensure verification, and it also recommended that work on solutions that satisfy the parties to the educational process should be worked on to overcome the crisis of low material returns to schools and their shortage in light of the Corona crisis.